Differences in optical properties of rat muscle tissue at room and physiological temperatures - Gamayunova, Ekaterina Алексеевна; Doronkina, Anna A.; Lazareva, Ekaterina Nikolaevna; Tuchina, Daria K.; Kochubey, Vyacheslav Ivanovich; Yanina, Irina Iur'evna (Известия Саратовского университета. Новая серия Серия: Физика, 2022)
Background and Objectives: Knowledge of the optical and thermal human tissues properties is essential for optimizing laser therapy and optical diagnostics. Most studies are carried out at room temperature of the sample. At the same time, it is known that the optical properties of biological tissues depend on temperature even in the physiological temperature range, that is, in the range of normal functioning of the body. Accordingly, there is a possibility that the use of literature data will lead to an incorrect assessment of the conditions for the propagation of light through biological tissue in a living object. Incorrect data on the optical properties of biological tissues at physiological temperature can lead to unreliable results in medical optical diagnostics or therapy. Therefore, studies of the temperature dependences of the optical properties of biological objects are undoubtedly topical. This work shows the differences in the optical properties of rat muscle tissue before and after heating the samples to physiological temperature. Materials and Methods: The spectra of collimated transmission, total transmission and diffuse reflection of rat muscle tissue were recorded. The spectra were recorded at 25°C (room temperature) and 38–39°C (physiological temperature). For each measured point of the sample, the spectral dependences of the absorption coefficients, transport scattering coefficient, and anisotropy factor of the studied samples were calculated. Results and conclusion: It has been shown that the optical properties of muscle tissue differ for room and physiological temperatures. In this case, the absorption and scattering coefficients practically do not change. The main parameter that changes with temperature is the anisotropy factor. This change also leads to a change in the transport scattering coefficient.